Combustion characteristics of ignition processes for lean premixed swirling combustor under visual conditions. (1st March 2021) - Shen, Wenkai; Liu, Li; Hu, Qiming; Liu, Guichuang; Wang, Jiwei; Zhang, Ning; Wu, Shaohua; Qiu, Penghua; Song, Shaowei
Abstract: The combustion characteristics of ignition processes under different ignition fuel ratios were studied on a natural gas-fueled micro gas turbine combustion chamber. With the changing of air mass flow, the equivalence ratio varied from 0.024 to 0.994 at which the fuel mass flow remained the same. The flue gas compositions were measured at the combustion chamber outlet, and used to calculate the combustion efficiency. To characterize the relative flame stability, optical measurements and digital image processing techniques were applied. The results indicate that the combustor can ignite successfully under the ignition fuel ratio conditions of 10%, 15%, and 20%, in which the corresponding equivalence ratios are 0.082–0.497, 0.082–0.746, and 0.098–0.994, respectively. Moreover, the combustion efficiency decreased with the descending equivalence ratio. However, the amount of CO and unburned CH4 in the combustion products increased as the equivalence ratio decreased. The heat release rate in the reaction zone and the morphological characteristics of the flame were obtained using the gray level of average flame images. Furthermore, the flame fluctuation was analyzed by coefficient of variation of the flame area, and the relative flame stability was analyzed by the probability distribution density of the relative flame area ratio. The appropriate equivalence ratios for ignition are around 0.245, 0.243–0.369, and 0.196–0.326 under the ignition fuel ratio conditions of 10%, 15%, and 20%. The ignition fuel ratio has considerable influence on combustion efficiency, combustion product, and flame stability. Highlights: Experiments of ignition process of a 300 kW micro gas turbine. Development of an flame analysis method based on high speed observable light imaging. Consideration of combustion efficiency and relative flame stability in selection. Big difference in the relative stability with different ignition operating conditions. The results show the proposed method can successfully capture the flame fluctuations.